The Phenomenon of Work-Family Conflict and Work Stress and Their Effect on Employee Performance - Ali Amran; Tri Lestari; Yunika Komalasari; Rofily Putriyandari; Yayu Sri Rahayu; Devi Yuniati Drajat (AIBPM Publisher, 2021)
The purpose of this research is to examine work-family conflict, work stress, and employee performance, as well as to determine the impact of work-family conflict and work stress on employee performance at PT Bank Mandiri Taspen KCP Ujungberung during the COVID-19 pandemic. The research method used in this study is a survey method. Descriptive and verificative surveys are the type of study used in this research by using multiple regression analysis. The sample in this research was 30 respondents from PT Bank Mandiri Taspen Branch of Ujung Berung - Bandung. Determination of respondents was taken by using the non-probability sampling method with the saturated sampling technique. The data used are the primary results obtained from distributing questionnaires. According to the findings of this study, there is a high level of work-family conflict, a high level of work stress at the company, and a high level of employee performance. Hypothesis testing shows that work-family conflict partially doesn’t have a significant impact on employee performance, work stress partially doesn’t have a significant impact on employee performance, and simultaneously work-family conflict and work stress do not have a significant impact on employee performance at PT Bank Mandiri Taspen Branch of Ujung Berung – Bandung.